Hierarchical nano-to-molecular disassembly of boron dipyrromethene nanoparticles for enhanced tumor penetration and activatable photodynamic therapy. (August 2021) - Zhang, Yonghe; Zhao, Ruibo; Liu, Jia; Kong, Hao; Zhang, Kebiao; Zhang, Yuan-Ning; Kong, Xiangdong; Zhang, Quan; Zhao, Yanli
Abstract: The development of activatable photosensitizers (PSs) is of particular interest for achieving tumor photodynamic therapy (PDT) with minimal side effects. However, the in vivo applications of PSs are limited by complex physiological and biological delivery barriers. Herein, boron dipyrromethene (BDP)-based nanoparticles are developed through the self-assembly of a multifunctional "one-for-all" building block for enhanced tumor penetration and activatable PDT. The nanoparticles show excellent colloidal stability and long circulation lifetime in blood. Once they reach the tumor site, the first-stage size reduction occurs due to the hydrolysis of the Schiff base bond between polyethylene glycol and the cyclic Arg-Gly-Asp peptide in the acidic tumor microenvironment (pH~6.5), facilitating tumor penetration and specific recognition by cancer cells overexpressing integrin αν β3 receptors. Upon the endocytosis by cancer cells, the second-stage size reduction is triggered by more acidic pH in lysosomes (pH~4.5). Importantly, the protonated diethylamino groups can block photoinduced electron transfer from the amine donor to the excited PSs and accelerate complete disassembly of the nanoparticles into single PS molecule, with the recovery of the fluorescence and photoactivity for efficient PDT. This study presents a smart PS delivery strategy involving acidity-triggered hierarchical disassembly from the nano to molecular scale for precise tumor PDT. Graphical abstract: Image 1